Cellulose‐Based Substrate for SERS‐Promoted Histamine Picomolar Detection in Beverages. Issue 11 (18th March 2019) - Bettini, Simona; Pal, Sudipto; Sawalha, Shadi; Licciulli, Antonio; Valli, Ludovico; Giancane, Gabriele; Pagano, Rosanna
Abstract: Histamine is a biogenic amine (BA) playing an important physiological role in human body, even though the assumption of high histamine amount from food and beverages can cause health diseases such as, for example, cutaneous allergy, headache and nausea. In fact, histamine can be present in foods and beverages as the result of microbial metabolism induced by temperatures and storage conditions, so histamine levels are commonly used as an indicator of food safety and quality. In the present contribution, the possibility to detect low concentration of histamine by Surface Enhanced Raman Spectroscopy (SERS) by using silver nanoparticles (AgNPs)‐cellulose hybrid substrate has been proposed. An easy procedure for the fabrication of the hybrid supports was developed and SERS effect at different AgNPs amounts was tested. The developed systems allowed detecting histamine down to 10–12 M in aqueous solutions. SERS substrates have been tested directly on two different kinds of commercial white wines, the first one stored in tetra pack and the other one in glass bottles without any pre‐treatment procedure. Histamine concentrations in the real samples were obtained by recording the corresponding Raman spectra and confirmed by means of conventional HPLC analysis. Abstract : Cellulose based SERS substrates decorated with AgNPs were synthetized by an easy procedure and were demonstrated to detect histamine in aqueous solutions down to 10 ‐12 M. A "hot spot" Surface Enhanced Raman Scattering mechanism allowed the identification of histamine even in real samples, without any pre‐treatment on the analysed samples.